2021
DOI: 10.3758/s13415-021-00895-9
|View full text |Cite|
|
Sign up to set email alerts
|

A win-win situation: Does familiarity with a social robot modulate feedback monitoring and learning?

Abstract: Social species rely on the ability to modulate feedback-monitoring in social contexts to adjust one’s actions and obtain desired outcomes. When being awarded positive outcomes during a gambling task, feedback-monitoring is attenuated when strangers are rewarded, as less value is assigned to the awarded outcome. This difference in feedback-monitoring can be indexed by an event-related potential (ERP) component known as the Reward Positivity (RewP), whose amplitude is enhanced when receiving positive feedback. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Support for this assumption comes from a recent neurophysiological study using the gambling task to examine whether familiarization with the robot Cozmo 1 modulates feedback processing after a one-time interaction: one group of participants engaged in a 20-minutes interaction with Cozmo (playing interactive games with the robot via the associated mobile app) and the other group played the Simon Says game (an interactive game that does not involve Cozmo) before gambling for themselves ("Self") or Cozmo ("Other"). The data shows larger RewP amplitudes and slower learning of the contingencies between color and chance of winning after one-time familiarization with Cozmo (Abubshait et al, 2021). Although this effect was not specific to the "Other" condition, but affected the "Self" condition as well, the results indicate that familiarization with a social robot does indeed modulate feedback-based learning in short-term interactions.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Support for this assumption comes from a recent neurophysiological study using the gambling task to examine whether familiarization with the robot Cozmo 1 modulates feedback processing after a one-time interaction: one group of participants engaged in a 20-minutes interaction with Cozmo (playing interactive games with the robot via the associated mobile app) and the other group played the Simon Says game (an interactive game that does not involve Cozmo) before gambling for themselves ("Self") or Cozmo ("Other"). The data shows larger RewP amplitudes and slower learning of the contingencies between color and chance of winning after one-time familiarization with Cozmo (Abubshait et al, 2021). Although this effect was not specific to the "Other" condition, but affected the "Self" condition as well, the results indicate that familiarization with a social robot does indeed modulate feedback-based learning in short-term interactions.…”
Section: Introductionmentioning
confidence: 78%
“…The paradigm presented here shows that a "hybrid" solution, that is: the combination of an unscripted interaction component and a scripted measurement component, is worth considering as it does not place significant constraints on the social interaction, but allows behavioral and neurophysiological correlates of social cognition to be obtained with high internal validity. A few early studies pioneering this approach have shown its feasibility for behavioral (current study), neurophysiological (e.g., Abubshait et al, 2021; "hybrid" with an ERP component) and neural (e.g., Cross et al, 2019; "hybrid" with fMRI component) outcome measures.…”
Section: Figure 6 Learning Rates As a Function Of Condition And Recipientmentioning
confidence: 84%
See 3 more Smart Citations